Tannery Industry and Its Sustainability in Bangladesh - Uddin Bhuiyah, Mohammad Saif; Kamal, Yousuf (Dhaka University Journal of Business Studies, 2023)
Understanding corporate sustainability is an important area of research for social and environmental researchers. Many businesses now face the challenge of sustainability with the increase of rapid awareness by the relevant stakeholders and growing concerns over the social and environmental issues. The notion of sustainability within the context of tannery industry is perceived to be more serious in terms of social and environmental perspectives. Tannery industry of Bangladesh is such a significant sector that deserves more attention from the researchers to explore the sustainability issues, however there is no such research in the context of Bangladesh to explore this issue. In this paper, we have attempted to measure the sustainability of the tannery industry by utilizing a Sustainability Information Disclosure Index (SIDI) and then we have tried to understand the disclosure quality of the tannery industry of Bangladesh. Our result shows that overall sustainability disclosure scenario of the companies in tannery industry is very disappointing (average SIDI only 25.04% during the year 2009 to 2018). Reporting on economic, environmental and social impacts are three important aspects of sustainability reporting. In this study, economic, environmental and social issues related disclosures have been found only 34.68%, 8.83% and 31.6% respectively. No disclosure has been found about ETP (Effluent Treatment Plants), water and solid waste disposal, greenhouse gas emission, pollution control equipment and policy ensuring efficiency in the use of energy and environment-friendly technologies which are very crucial for tannery industry. Journal of Business Studies, Vol. XLII, No. 2, August 2021 Page 139-160